Effects of daily light integral on tomato (Solanum Lycopersicon L.) grafting and quality in a controlled environment - Song, Jinxiu; Fan, Yulong; Li, Xingqun; Li, Yuzhu; Mao, Hanping; Zuo, Zhiyu; Zou, Zhirong (International Journal of Agricultural and Biological Engineering, 2022)
As the source of energy and biology signals, light can influence the healing process of grafted seedlings by regulating the synthesis of the endogenous hormone, regeneration of wound-healing tissue, and connection of vascular tissue in grafted seedlings. The effect of daily light integral (DLI) on the healing process and seedling quality of tomato (Solanum lycopersicum L.) was analyzed in this study, with the comparison of grafted seedlings treated in dark for 7 d after grafting. The results showed that the height increment of scion and rootstock, adhesion of graft union, stem flow, total chlorophyll content, and net photosynthesis rate increased gradually with increasing light intensity, and no longer increased significantly when the DLI was higher than 5.04 mol/m2•d. The contents of auxin (IAA) and gibberellin (GA) in tomato leaves increase and abscisic acid (ABA) decreases with the increase of DLI. However, there was no significant difference between the treatments with DLI higher than 6.48 mol/m2•d. Both the biomass and energy use efficiency (EUE) of grafted seedlings increased with DLI in a certain range and then decreased. The biomass was the largest when DLI was 5.04 mol/m2•d. However, EUE was highest when DLI was 7.46 mol/m2•d. In conclusion, a suitable DLI is beneficial to cultivate high-quality grafted tomato seedlings, and increasing DLI within a certain range can promote biomass accumulation, connection of vascular tissue, endogenous hormone biosynthesis in tomato grafted seedlings during healing period. The lighting environment with DLI of 5.04 mol/m2•d (light intensity of 100 μmol/m2•s and light time of 14 h/d) is recommended for the healing treatment in high-quality production, which also improves EUE during the healing period of tomato grafted seedlings.Keywords: stress resistance, endogenous hormones, stem flow, energy use efficiency, seedling indexDOI: 10.25165/j.ijabe.20221506.7409Citation: Song J X, Fan Y L, Li X Q, Li Y Z, Mao H P, Zuo Z Y, et al. Effects of daily light integral on tomato (Solanum Lycopersicon L.) grafting and quality in a controlled environment. Int J Agric & Biol Eng, 2022; 15(6): 44–50.